IMPROVING MICRO, SMALL, AND MEDIUM ENTERPRISE OWNERS’ MARKETING SKILL THROUGH ACTIVE LEARNING BASED DIGITAL MARKETING TRAINING - Rahmawan, Agus; Nurhayati, Sri (Jurnal Empowerment, 2025)
This study aims to detail the implementation of active learning-based digital marketing training to enhance the marketing capabilities of micro, small, and medium-sized enterprises (MSMEs). This research employs a qualitative, descriptive methodology. The gathering of data commenced with interviews and observations of 12 informants, including 10 MSME owners, 1 trainer, and a training organizer. Utilizing semi-structured interviews, participatory observation, and documentation studies, information was gathered. Triangulation was then applied to the data for analysis. This study reveals that 1) planning includes determining training learning needs, preparing schedules, determining trainers, determining the location and time of training, determining participant recruitment requirements, determining the form and materials of training materials, and digital marketing. Initial activities include pre-testing and orientation of digital marketing training based on active learning. Core activities include explanations of digital marketing materials for MSMEs and practices for developing MSMEs' digital marketing strategies. Final activities include evaluating the success of the implementation. 3) The results of the training include a significant increase in marketing knowledge and abilities, as seen in the post-test score. This study indicates that micro, small, and medium-sized enterprises (MSMEs) should receive active learning-based digital marketing training on a regular basis in order to increase their competitiveness and economic influence.